RI 2378 Determination Of Suspended Matter In Gases By Collection On Filter Paper - S. H. Katz (The National Institute for Occupational Safety and Health (NIOSH), 1922)
Tar and suspended matters are removed from manufactured gas used for domestic and industrial purpose.